Modern application of Siyar (Islamic law of nations): some preliminary observations - Ahamat, Haniff (2009)
Siyar is the Islamic version of international law. It is a branch of fiqh that governs relations between the states. There are considerably rich literature on the evolution of siyar as a discipline of Islamic science from the time siyar was discussed by Abu Hanifah and later Abu Yusuf to the time their views were refined by al-Shaybani and further developed and criticized by al-Sarakhsi and al-Awza'i respectively.